2021
DOI: 10.3389/fimmu.2021.657622
|View full text |Cite
|
Sign up to set email alerts
|

ILC3, a Central Innate Immune Component of the Gut-Brain Axis in Multiple Sclerosis

Abstract: Gut immune cells have been increasingly appreciated as important players in the central nervous system (CNS) autoimmunity in animal models of multiple sclerosis (MS). Among the gut immune cells, innate lymphoid cell type 3 (ILC3) is of special interest in MS research, as they represent the innate cell counterpart of the major pathogenic cell population in MS, i.e. T helper (Th)17 cells. Importantly, these cells have been shown to stimulate regulatory T cells (Treg) and to counteract pathogenic Th17 cells in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 129 publications
(164 reference statements)
0
11
0
Order By: Relevance
“… 30 The gut microenvironment was found to have the ability to modulate the activation and differentiation of autoreactive T cells and guide them to the CNS. 37 …”
Section: Discussionmentioning
confidence: 99%
“… 30 The gut microenvironment was found to have the ability to modulate the activation and differentiation of autoreactive T cells and guide them to the CNS. 37 …”
Section: Discussionmentioning
confidence: 99%
“…These cells are well known for their ability to maintain the integrity of the intestinal barrier and to shape the immune response to gut microbiota through an IL-22-dependent pathway. 10,11 All these changes alter immune homeostasis in the gut and make the host more susceptible to the overgrowth of opportunistic pathogens and intestinal infections.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the composition of the gut microbiota are closely related to changes in the levels of inflammatory factors, for example, the levels of GM-CSF, IL-12p70, IL-15, IL-1RA, IL-9, IL-23 and TNF-a increased, and the levels of IL-10 decreased in ICH patients. This study indicated that an increase in Enterococcus and a decrease in Prevotella increased the risk of ICH [43]. Thus, the diversity of the gut microbiota decreased after ICH, as some phyla and genera increased in abundance, and some decreased.…”
Section: Gut Microbiota Dysbiosis Is Induced After Ichmentioning
confidence: 63%
“…However, in the late stages of ICH, dendritic cells in the mesenteric lymph nodes promote the migration of Treg cells to the intestine, thereby inhibiting the differentiation of IL-17-producing γδ T cells and attenuating the migration of γδ T cells from the gut to the brain and ultimately protecting against cerebral ischemia/reperfusion injury [45]. the levels of GM-CSF, IL-12p70, IL-15, IL-1RA, IL-9, IL-23 and TNF-a increased, and the levels of IL-10 decreased [43] In addition, gut bacteria generate neuroactive compounds and mediate neuronal functions, thus affecting the behavior after ICH. Previous research demonstrated that the gut microbiota affects the host homeostasis through bile acid metabolism, amino acid metabolism and metabolic pathways such as those involving SCFAs.…”
Section: Gut Dysbiosis Exacerbates the Neuroinflammatory Response Of Ichmentioning
confidence: 99%